Effect of probiotic doses em-4 (effective microorganism-4) in commercial feed on increased growth and survival of siamese catfish (Pangasius hypophthalmus) - Simamora, Santi Desima; Febri, Suri Purnama; Rosmaiti, Rosmaiti (Universitas Malikussaleh, 2021)
There are several types of catfish, one of which is siamese catfish which has a scientific name (Pangasius hypopthalmus). Often the farmers spend money on fish feed there are not many farmers who are able to find out how to give to fish without hugging the feed that many of them are adding probiotics EM-4 The purpose of this study is to analyze the influence of probiotic feed EM-4 on feed to the growth and survival of fish siamese catfish. This study was conducted in Green House Universitas Samudra using RAL consisting of 4 treatments and 5 replays is P1 (probiotic administration EM-4 0ml/kg), P2 (probiotic administration EM-4 10ml/kg), P3 (probiotic Administration 15ml/kg), P4 (probiotic administration 20ml/kg). The meters observed are SR, weight growth, long growth, daily growth rate, FCR, feed efficiency, water quality. The results of this study showed that the treatment of the addition of EM-4 probiotics in catfish had a noticeable effect on the growth of absolute weight, absolute length growth, daily growth rate, and had no noticeable effect on SR, FCR, feed efficiency. The highest weight growth and length was in the P3 treatment (dose addition 15ml/kg) with a total weight of 8.5 gr and length 5.6 cm. Keywords: Probiotic Em-4; Pangasius hypopthalmus; Growh; Survival.